Quarkyonic solution to the hyperon puzzle - Fujimoto Yuki; Kojo Toru; McLerran Larry (EPJ Web of Conferences, 2025)
We show that Quarkyonic Matter can mitigate the hyperon puzzle. The key observation is that the hyperon threshold is shifted to a higher density by a factor of constituent strange quark mass. We illustrate this effect by using the ideal dual Quarkyonic (IdylliQ) model with multiple flavors.